Ternary porous metal oxides, methods for their preparation and catalysts

CN118062900BActive Publication Date: 2026-11-03CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410360599.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-27
Publication Date
2026-11-03
Estimated Expiration
2044-03-27

AI Technical Summary

Technical Problem

现有柴油机废气中烟尘颗粒和氮氧化物的氧化效率低,催化剂与烟灰接触不充分,导致再生温度高、燃料消耗增加,且现有多孔材料合成方法复杂且不环保。

Method used

A stepwise calcination method was used to prepare ternary porous metal oxides. By impregnating a metal precursor solution with a microsphere template agent and then performing stepwise calcination, an ordered macroporous structure was formed, ensuring uniform distribution of metal elements and improving catalytic activity.

Benefits of technology

To maintain stable NOx oxidation activity with low catalyst dosage, reduce regeneration temperature, increase catalyst specific surface area and activity, and enhance flue gas oxidation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118062900B_ABST
    Figure CN118062900B_ABST
Patent Text Reader

Abstract

The application provides a ternary porous metal oxide and a preparation method and a catalyst thereof. The preparation method comprises the following steps: dipping a microsphere template agent into a solution of metal precursors, and sequentially performing first calcination and second calcination on the dipped microsphere template to obtain the ternary porous metal oxide; wherein the metal precursors comprise a cerium source, a manganese source and an alkali metal source; the temperature of the first calcination is 300-350 DEG C, and the time of the first calcination is 3-4 h; the temperature of the second calcination is 500-550 DEG C, and the time of the second calcination is 4-4.5 h. The application further provides the ternary porous metal oxide obtained by the above preparation method and a catalyst comprising the ternary porous metal oxide. The ternary porous metal oxide provided by the application has an ordered large pore structure, and has the characteristics of large surface area, uniform element distribution, good structural stability, high catalytic activity and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of macroporous material preparation technology, and in particular to a ternary porous metal oxide, its preparation method, and catalyst. Background Technology

[0002] The main air pollutants emitted from diesel engine exhaust are particulate matter and nitrogen oxides, which are highly hazardous. Particulate matter can cause serious respiratory illnesses and cancer, while nitrogen oxides are considered a contributor to acid rain, photochemical smog, ozone depletion, and the greenhouse effect. Particulate matter in diesel vehicle exhaust is typically removed from the exhaust by filtration through ceramic filters. When these filters become clogged with particulate matter, they require periodic regeneration. This process raises the filter temperature, causing the soot to oxidize. The increased back pressure due to soot deposits and the elevated temperatures required for filter regeneration are associated with increased fuel consumption, necessitating the development of improved soot oxidation catalysts that can lower the regeneration temperature. As a gas / solid / solid interaction, the contact between the soot and the catalyst is crucial, and the catalytic effect strongly depends on the degree of mixing between the soot and the catalyst. In laboratory tests, oxidation occurs at significantly lower temperatures (typically 100–200°C) when the soot and catalyst are crushed together (so-called close contact), rather than when they are lightly mixed (so-called loose contact). In close contact, a broad interface is established between the main soot particles and the catalyst, but in loose contact, the interface is limited to isolated contact points between larger clusters of main particles. Driven by increasingly stringent emission standards, the development and application of aftertreatment catalytic technologies for reducing major air pollutants from diesel engines have grown dramatically over the past few decades.

[0003] Soot primarily forms in areas of poor fuel-air mixing and combustion, i.e., far from the main oxidation zone. This is because a lean mixture causes excessively low cylinder temperatures, weakening the combustion process and reducing the ability to oxidize soot in the later stages of combustion. Oxidation can occur both inside and on the surface of the primary soot particles. The initial combustion of soot particles is rapid and instantaneous, consuming nearly 20% of the carbon in the particles, while secondary combustion occurs inside these spherical particles, leading to the formation of porous spheres. However, internal combustion and oxidation on the outer surface of the particles can cause soot aggregates to break up, resulting in an increase in total soot concentration. For the small particles generated by oxidation-induced fragmentation, they are completely oxidized when the temperature decreases; while at higher temperatures, not only is the oxidation process more complete, but the likelihood of internal combustion also decreases, thus reducing the particle number concentration. In the later stages of combustion, oxidation dominates; however, due to low combustion temperatures and insufficient oxygen, the particles cannot be completely oxidized.

[0004] The oxidation reactivity of soot is primarily driven by the disorder of carbonaceous nanostructures and the increase in edge-accessible carbon, with little relation to surface oxygen content. Due to differences in structure and surface composition, newly formed soot exhibits significantly higher surface oxidation reactivity than graphitized soot. Given sufficient oxidant penetration into the soot surface, more active soot particles will be completely oxidized. Furthermore, the soot initiation limit and oxidation process are the main factors influencing soot oxidation reactivity. A lower soot initiation rate reduces the number of particles and increases the average particle diameter, leading to easier surface oxidation for the same soot mass, thus resulting in a lower oxidation rate. Additionally, the soot oxidation rate is related to O2 concentration. Measures that enhance turbulence and mixing, such as strengthening the interaction between primary and secondary injections, are beneficial for increasing the soot oxidation process.

[0005] With increasing emphasis on the development of green chemistry, it is becoming increasingly important to develop a new, environmentally friendly, and simple method for synthesizing ordered macroporous metal oxides. Summary of the Invention

[0006] To address the aforementioned problems, the present invention aims to provide a ternary porous metal oxide, its preparation method, and a catalyst. This porous material maintains stable NOx oxidation activity with minimal catalyst dosage, and the metal elements are uniformly distributed throughout the material, resulting in high specific surface area and catalytic activity.

[0007] To achieve the above objectives, the present invention provides a method for preparing ternary porous metal oxides, the method comprising:

[0008] The microsphere template agent is impregnated in a solution of metal precursor, and the impregnated microsphere template is subjected to a first calcination and a second calcination in sequence to obtain the ternary porous metal oxide.

[0009] The metal precursor includes a cerium source, a manganese source, and an alkali metal source;

[0010] The first calcination temperature is 300-350℃, and the first calcination time is 3h-4h;

[0011] The second calcination temperature is 500-550℃, and the second calcination time is 4h-4.5h.

[0012] In the above preparation method, the microsphere template agent is generally a polymer microsphere generated by a polymerization reaction of monomers initiated by an initiator. The microsphere template agent obtained in this way is generally an ordered arrangement of microspheres.

[0013] In the above preparation method, the particle size of the microsphere template agent is 300nm-500nm, for example, it can be a specific value such as 300nm, 350nm, 400nm, 450nm, 500nm, etc., or a range with any two of the above specific values ​​as endpoints.

[0014] In the above preparation method, the microsphere template agent may include polymethyl methacrylate microspheres.

[0015] In the above preparation method, the preparation method of the polymethyl methacrylate microspheres may include: mixing methyl methacrylate with an initiator in a protective atmosphere and carrying out a polymerization reaction to obtain the polymethyl methacrylate microspheres.

[0016] In the above method for preparing polymethyl methacrylate microspheres, the mass ratio of methyl methacrylate to initiator can be controlled as 113-113.2:0.2-0.6.

[0017] In the above method for preparing polymethyl methacrylate microspheres, the methyl methacrylate can be purified methyl methacrylate. The purification process can involve rotary evaporation of the methyl methacrylate to remove polymerization inhibitors. Specifically, this purification process can include: distilling the methyl methacrylate under reduced pressure at 40°C to obtain purified methyl methacrylate.

[0018] In the above-mentioned method for preparing polymethyl methacrylate microspheres, the initiator may include potassium persulfate, etc.

[0019] In the above method for preparing polymethyl methacrylate microspheres, the initiator can be a purified initiator. The purification process of the initiator may include: dissolving the initiator in water to form an initiator solution (the dissolution temperature can be 40°C), cooling with ice water to crystallize, filtering the crystals and washing them with ice water until no sulfate ions are present in the washing solution. The washed crystals are then dried under vacuum and stored in a sealed container. During the above purification process, the crystals obtained can be white needle-like crystals; sulfate ions can be tested with barium chloride solution; the absence of precipitate after mixing the washing solution with barium chloride solution indicates the absence of sulfate ions; the drying temperature can be 50°C, and the drying time can be more than 12 hours; vacuum drying avoids the decomposition of potassium persulfate.

[0020] In the above method for preparing polymethyl methacrylate microspheres, before mixing the initiator with methyl methacrylate, the initiator (e.g., a purified initiator) and methyl methacrylate can be heated separately to the temperature required for the polymerization reaction, and then the heated initiator is mixed with the heated methyl methacrylate. During the heating process of the initiator, it can be dissolved in water first, and the mixture is stirred while heating. The stirring speed is 300-350 rpm / min.

[0021] In the above-mentioned method for preparing polymethyl methacrylate microspheres, the process of mixing the initiator with methyl methacrylate may specifically include: heating the methyl methacrylate solution to the temperature of the polymerization reaction, heating the initiator to the temperature of the methyl methacrylate, and then mixing the methyl methacrylate with the initiator to form a raw material solution for the polymerization reaction.

[0022] In the above method for preparing polymethyl methacrylate (PMMA) microspheres, the particle size of the PMMA microspheres can be controlled by controlling the temperature of the polymerization reaction. Specifically, the polymerization reaction temperature can be 70-90°C, forming PMMA microspheres with a particle size of 300 nm-500 nm. In some specific embodiments, the polymerization reaction temperature can be specific values ​​such as 70°C, 75°C, 80°C, 85°C, and 90°C, or a range with any two of these specific values ​​as endpoints.

[0023] In the above method for preparing polymethyl methacrylate microspheres, the polymerization reaction time can be 1h-2h, for example, specific values ​​such as 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h, and any two of the above specific values ​​as endpoints.

[0024] In the above method for preparing polymethyl methacrylate microspheres, the polymerization reaction can be carried out under a protective atmosphere to avoid over-polymerization of the monomers. Specifically, the protective atmosphere can be a nitrogen atmosphere.

[0025] In the above method for preparing polymethyl methacrylate microspheres, the polymerization reaction may be accompanied by stirring. The stirring speed may be 3000-3500 rpm / min, and the stirring time may be 1h-2h, or more specifically 1.5h-2h.

[0026] In some specific implementations, the polymethyl methacrylate microspheres obtained by polymerization can be fluorescent green.

[0027] In the above-described method for preparing polymethyl methacrylate microspheres, the method further includes a post-treatment step on the polymerization product. The post-treatment may include filtering, centrifuging, and drying the polymerization product. The filtration and drying processes promote the ordered arrangement of the polymerized microspheres. The centrifugation process may be low-speed, long-duration centrifugation to promote the ordered arrangement of the microspheres. Specifically, the centrifugation speed may be 3000-3500 rpm / min, and the centrifugation time may be 10-11 hours.

[0028] In the above preparation method, the present invention uses neatly arranged microspheres as template agents, then impregnates the metal precursor solution in the gaps of the microspheres, removes the template agent microspheres through a calcination process, and finally obtains a ternary porous metal oxide with a highly ordered pore structure and a certain mechanical strength. Furthermore, the pore size in the ternary porous metal oxide can be adjusted according to the size of the microsphere template agent.

[0029] In the above preparation method, the molar ratio of the cerium source to the manganese source is generally controlled to be 1-6:1-10, for example, it can be specific values ​​such as 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc., or a range with any two of the above specific values ​​as endpoints. The molar ratio of the cerium source to the manganese source is generally controlled to be 1-5:1-5.

[0030] In the above preparation method, the cerium source may include cerium salt. The manganese source may include manganese salt.

[0031] In the above method for preparing ternary porous metal oxides, the metal precursor can be a soluble salt of a metal, and the anion of the metal precursor can include acetate and / or nitrate. Accordingly, the cerium source can include cerium nitrate and / or cerium acetate, and the manganese source can include manganese nitrate and / or manganese acetate.

[0032] In the above preparation method, the metal precursor further includes an alkali metal source. Compared to binary porous metal oxides formed by cerium and manganese sources, ternary porous metal oxides formed by cerium, manganese, and alkali metal sources have a higher active oxygen content. 3+ / Ce 4+ The ratio changes, resulting in better NOx oxidation performance. Specifically, the alkali metal element (hereinafter referred to as alkali metal) in the alkali metal source can include one or more combinations of lithium, sodium, and potassium. In some specific embodiments, the alkali metal source can be in the form of an alkali metal salt (e.g., a soluble alkali metal salt), which can include one or more combinations of sodium nitrate, potassium nitrate, and lithium nitrate. The lithium nitrate can be in hydrate form, such as lithium nitrate trihydrate.

[0033] In the above preparation method, the molar ratio of the alkali metal source to the cerium source can be controlled to be 0.2-0.5:1, such as 0.2:1, 0.3:1, 0.04:1, 0.5:1, etc., and a range with any two of the above specific values ​​as endpoints.

[0034] In the above-described method for preparing ternary porous metal oxides, the solvent used in the metal precursor solution is generally an organic solvent used to dissolve the metal precursor. The organic solvent may include ethylene glycol and / or methanol, for example, a combination of ethylene glycol and methanol; further, the organic solvent may be a combination of methanol and ethylene glycol in a volume ratio of 1:4. Methanol can be used to dissolve the cerium source, and ethylene glycol can be used to dissolve the manganese source.

[0035] In the above-mentioned method for preparing ternary porous metal oxides, the dissolution temperature is generally around 40-50℃ during the process of dissolving the metal precursor to form a solution. Stirring can be used during the dissolution process to promote uniform dissolution, and the stirring speed can be 400-500 rpm / min, for example, 400-450 rpm / min.

[0036] In preparing the metal precursor solution, the cerium source, manganese source, and alkali metal source can be added together to the aforementioned organic solvent for dissolution. The dissolution temperature can be controlled at 40-50℃, and the dissolution process can be accompanied by stirring to promote uniform dissolution. The stirring speed can be controlled at 400-450 rpm / min. Alternatively, a portion of the organic solvent can be used to dissolve the cerium source and alkali metal source, and the remaining organic solvent can be used to dissolve the manganese source. Then, the dissolved cerium source, alkali metal source, and manganese source are mixed to form the metal precursor solution. For example, the cerium source and alkali metal source can be dissolved in methanol at a temperature controlled at 40-50℃, accompanied by stirring at a speed of 400-500 rpm / min to obtain a mixed solution of cerium source and alkali metal source; the manganese source can be dissolved in ethylene glycol at a temperature controlled at 40-50℃, accompanied by stirring at a speed of 400-500 rpm / min to obtain a manganese source solution; the mixed solution of cerium source and alkali metal source and the manganese source solution are then mixed to obtain the metal precursor solution.

[0037] In the above-mentioned method for preparing ternary porous metal oxides, the mass ratio of the cerium source contained in the metal precursor to the microsphere template agent is 1-11:3.

[0038] In some specific implementations, the actual amount of the microsphere template agent can be 3-6g, for example, it can be a specific value such as 3g, 4g, 5g, 6g, or a range with any two of the above specific values ​​as endpoints.

[0039] In the above-mentioned method for preparing ternary porous metal oxides, after the microsphere template agent is mixed with the solution of the metal precursor, the appearance of bubbles on the surface of the microsphere template agent indicates that the metal precursor solution has begun to enter the interior of the microsphere template agent, and this time can be taken as the start time of impregnation.

[0040] In the above-mentioned method for preparing ternary porous metal oxides, the impregnation time can be more than 12 hours, and the impregnation temperature can be room temperature, specifically around 40°C.

[0041] In the above-mentioned method for preparing ternary porous metal oxides, the impregnation process can be carried out under vacuum conditions to promote the penetration of the metal precursor solution into the microsphere template agent.

[0042] In the above-mentioned method for preparing ternary porous metal oxides, the preparation method may include filtering and drying the impregnated microsphere template agent, followed by a first calcination. The drying temperature may be 40-60℃, and the drying time may be 12-24 hours.

[0043] In the above preparation method, through calcination, the metal precursor is converted into metal oxide. The metal oxide anti-topological microspheres form an ordered structure, and removing the microsphere template agent yields a macroporous structure with an ordered arrangement. Existing methods for removing the template agent include chemical removal and one-step calcination removal: chemical removal cannot completely remove the template agent, while conventional one-step calcination methods, although able to completely remove the template agent, can lead to the deterioration or even destruction of the porous structure formed by the metal oxide. This invention, through stepwise calcination and controlled calcination temperature, can completely remove the template agent while protecting the ordered macroporous structure of the metal oxide from damage.

[0044] In the above preparation method, by controlling the first calcination temperature, the template agent can be completely removed and the porous structure can be protected from damage.

[0045] In the above preparation method, the temperature of the first calcination is 300-350℃, for example, specific values ​​such as 300℃, 310℃, 320℃, 330℃, 340℃, 350℃, etc., and a range with any two of the above specific values ​​as endpoints. The time of the first calcination is 3h-4h, for example, specific values ​​such as 3h, 3.1h, 3.2h, 3.3h, 3.4h, 3.5h, 3.6h, 3.7h, 3.8h, 3.9h, 4h, etc., and a range with any two of the above specific values ​​as endpoints.

[0046] In the above preparation method, the first calcination process further includes heating from room temperature (around 30°C) to the first calcination temperature, and the heating rate can be controlled at 1°C / min.

[0047] In the above preparation method, the second calcination process can promote the formation of metal oxides (cerium oxide, manganese oxide, alkali metal oxides, etc.). The temperature of the second calcination is 500-550℃, for example, specific values ​​such as 500℃, 510℃, 520℃, 530℃, 540℃, 550℃, etc., and a range with any two of the above specific values ​​as endpoints. The time of the second calcination is 4h-4.5h, for example, specific values ​​such as 4h, 4.1h, 4.2h, 4.3h, 4.4h, 4.5h, etc., and a range with any two of the above specific values ​​as endpoints. The ternary porous metal oxide provided by the present invention includes manganese oxide. Compared with other catalytic metal oxides, manganese oxide has higher NO-TPO activity; however, manganese oxide has low thermal stability, and if a one-step calcination method is used, the mesoporous structure of manganese oxide will collapse. This invention separates the template removal process from the oxide formation process. First, a lower calcination temperature (first calcination) is used to remove the microsphere template and stabilize the cerium-manganese structure, and then a higher calcination temperature (second calcination) is used to promote the formation of metal oxides.

[0048] In the above preparation method, the second calcination process further includes raising the temperature from the first calcination temperature to the second calcination temperature, and the rate of temperature increase can be controlled at 1℃ / min.

[0049] In the above-mentioned method for preparing ternary porous metal oxides, the first calcination and the second calcination process can be carried out by placing the microsphere template agent completely impregnated with metal salt into a tube furnace, and the calcination atmosphere can be an air atmosphere.

[0050] According to a specific embodiment of the present invention, the preparation method of the above-mentioned ternary porous metal oxide may include:

[0051] In a protective atmosphere, methyl methacrylate is used as a monomer, and an initiator initiates the polymerization reaction of the monomer to generate polymer microspheres, which serve as templates for ordered microspheres.

[0052] The microsphere template agent is immersed in a solution of the metal precursor. During the immersion process, a vacuum is drawn. The fully immersed microsphere template agent is filtered, dried, and then subjected to a first calcination and a second calcination to obtain the ternary porous metal oxide.

[0053] Specifically, the preparation method of the above-mentioned ternary porous metal oxide may include:

[0054] 1. Nitrogen gas, used as a protective gas, is introduced into a four-necked flask. Then, purified methyl methacrylate and deionized water are added to the flask. The mixture is stirred and heated to 70-90°C to form the first solution. Simultaneously, the purified initiator is heated to 70-90°C and stirred to dissolve, forming an initiator solution. The dissolved potassium persulfate solution is then poured into the first solution to carry out the polymerization reaction. The mixture is stirred uniformly in a sealed environment for 1-2 hours. After the polymerization reaction is complete, the filtrate is filtered. The filtrate is centrifuged at 3000 rpm / min for 10-11 hours. After centrifugation, the filtrate is dried for 24 hours to obtain methyl methacrylate microspheres.

[0055] 2. Preparation of metal precursor solution:

[0056] A methanol and ethylene glycol solution with a volume ratio of 1:4 was prepared as an organic solvent. A cerium source, a manganese source, and an alkali metal source were added to the organic solvent, with a molar ratio of alkali metal source to cerium source of 0.2-0.5:1 and a molar ratio of cerium source to manganese source of 1-6:1-10. After heating and stirring, the solution was fully dissolved to obtain a metal precursor solution. A microsphere template agent was added to this solution, with a mass ratio of cerium source to microsphere template agent of 1-11:3. The solution was vacuum impregnated for 24 hours, filtered, and dried. The microsphere template agent completely impregnated with the metal salt (…) Generally, the fragments are placed in a tube furnace and subjected to the following calcination process in an air atmosphere: the temperature is increased from 30°C to 300°C-350°C at a rate of 1°C / min, and held at 300°C-350°C for 3-4 hours for the first calcination; then the temperature is increased from 300°C to 500-550°C at a rate of 1°C / min, and held at 500-550°C for 4-4.5 hours for the second calcination, to obtain the ternary porous metal oxide, which has an ordered macroporous structure.

[0057] The present invention also provides a ternary porous metal oxide, which is obtained by the above preparation method.

[0058] According to specific embodiments of the present invention, the ternary porous metal oxide exhibits high structural stability and a porous structure, with the pores generally being macropores. In some specific embodiments, the pore size of the ternary porous metal oxide is generally 200nm-350nm, specifically 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm, 310nm, 320nm, 330nm, 340nm, 350nm, etc., and a range with any two of the above specific values ​​as endpoints.

[0059] According to a specific embodiment of the present invention, the ternary porous metal oxide contains a framework in which the voids are uniformly distributed and periodically arranged, exhibiting a three-dimensional ordered macroporous structure. As the alkali metal element content in the ternary porous metal oxide increases, nanoparticles gradually appear on the surface of the framework, and the number of nanoparticles gradually increases.

[0060] According to a specific embodiment of the present invention, the pore wall thickness of the ternary porous metal oxide can be 25 nm-40 nm. The ternary porous metal oxide has uniform pore size, window size, and wall thickness, with the macropores exhibiting a highly periodic arrangement. In some specific embodiments, windows may connect the macropores. The ternary porous metal oxide typically has structurally stable windows.

[0061] According to a specific embodiment of the present invention, the ternary porous metal oxide contains cerium, manganese, and alkali metals. Cerium-based materials possess variable oxidation states and the ability to generate oxygen vacancies, thus exhibiting high oxygen storage capacity and excellent reducing properties, making them widely applicable for NOx oxidation and soot combustion. Mn-based metal oxides, as p-type semiconductors, have a greater oxygen adsorption capacity compared to n-type semiconductor Zn oxides, and the adsorbed O2 dissociates into O. - This is more conducive to deep oxidation. The oxides of the alkali metals can further enhance the activity of the cerium-manganese oxide catalyst. Therefore, the ternary material formed by cerium-manganese alkali metals exhibits excellent activity for NOx oxidation.

[0062] This invention also provides a catalyst comprising, or made from, the aforementioned ternary porous metal oxide. The aforementioned ternary porous metal oxide has an ordered macroporous structure, resulting in a high specific surface area and exposed active sites; furthermore, the elemental distribution is uniform, the active sites are dispersed, and the morphology is uniform. Therefore, this ternary porous metal oxide exhibits high catalytic activity when applied as a catalyst (e.g., in the purification of exhaust gases). According to a specific embodiment of this invention, the catalyst can be a CO oxidation catalyst or a NOx oxidation catalyst; that is, the catalyst provided by this invention can be applied to CO catalytic oxidation processes and NOx catalytic oxidation processes.

[0063] The beneficial effects of this invention include:

[0064] The ternary porous metal oxide prepared by the method provided by this invention has an ordered macroporous structure and uniform distribution of metal elements. It has the characteristics of large surface area, uniform element distribution, high activity, high purity, non-agglomeration, and good stability, and can be applied to diesel engine exhaust gas treatment. The addition of an appropriate amount of alkali metal is beneficial to increase the active oxygen content, thereby further improving the performance of cerium-manganese catalyst. Attached Figure Description

[0065] Figures 1 to 4 The images shown are, in order, scanning electron microscope (SEM) images of porous cerium manganese oxides from Comparative Examples 1 to 4.

[0066] Figure 5 This is a scanning electron microscope image of porous cerium oxide, Comparative Example 13.

[0067] Figure 6 This is a scanning electron microscope image of porous manganese oxide, Comparative Example 14.

[0068] Figures 7 to 10 The images shown are, in order, energy dispersive X-ray (EDS) elemental spectra of porous cerium manganese oxides from Comparative Examples 1 to 4.

[0069] Figure 11 The diagram shows the temperature program curves for the porous cerium manganese oxides obtained in Comparative Examples 1, 2, 3, 4, 13, and 14, as well as the low-temperature catalytic oxidation of NO.

[0070] Figure 12 The NO conversion results are for the porous ternary metal oxides of Examples 1 to 4.

[0071] Figure 13 The NO conversion results are for the porous ternary metal oxides of Examples 5 to 7.

[0072] Figure 14 The NO conversion results are for the porous ternary metal oxides of Examples 8 to 11.

[0073] Figure 15 The results show the catalytic stability test results of the porous cerium manganese oxide in Comparative Example 2.

[0074] Figure 16 This is a SEM image of the microsphere template agent prepared in Example 1.

[0075] Figures 17 to 27 The images shown are scanning electron microscope (SEM) images of the ternary porous metal oxides from Examples 1 to 11, respectively.

[0076] Figures 28 to 31 The images shown are, in order, energy dispersive X-ray elemental spectra of the ternary porous metal oxides prepared in Examples 1, 2, 5, and 6.

[0077] Figure 32 The results show the catalytic stability test results of the porous cerium manganese oxide in Example 5. Detailed Implementation

[0078] In order to provide a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention will now be described in detail below, but it should not be construed as limiting the scope of implementation of the present invention.

[0079] Comparative Example 1

[0080] This comparative example provides a method for preparing binary porous metal oxides, including the following steps:

[0081] 1. Pour 120 ml of purified methyl methacrylate into a 1000 ml four-necked flask, then add 450 ml of deionized water to form a methyl methacrylate solution. Pour nitrogen gas through the solution and turn on the condenser.

[0082] Potassium persulfate was heated to dissolve it. The mixture was stirred at 300 rpm / min and heated to 80°C. Once the solution in the four-necked flask reached 80°C, the potassium persulfate solution at 80°C was added to the four-necked flask containing the methyl methacrylate solution to carry out the polymerization reaction. The mixture was stirred for 1-2 hours.

[0083] The polymerization product was filtered, and the filtrate was placed in a 50 mL centrifuge tube and centrifuged at 3000 rpm / min for 10–11 hours. After drying for 24 hours, ordered microsphere templates were obtained. These microsphere templates were fluorescent green.

[0084] 2. Place 1 gram of cerium nitrate hexahydrate and 0.56 grams of manganese acetate tetrahydrate into a 100 ml beaker, then pour in 50 ml of methanol and ethylene glycol in a volume ratio of 1:4. Turn on the stirrer and set it to 500 rpm / min to heat to 50°C. Stir until the metal salt is completely dissolved to obtain a metal precursor solution.

[0085] Three grams of dried microsphere template agent were added to the above metal precursor solution and vacuum impregnated for 24 hours. The impregnated fragmented microsphere template agent was filtered and dried for 24 hours. The fragmented microspheres completely impregnated with metal salt were placed in a tube furnace and calcined by air circulation. First, the temperature was heated to 300°C and held for 3 hours for the first calcination. Then, the temperature was heated to 550°C and held for 4 hours for the second calcination to obtain porous cerium manganese oxide. This porous cerium manganese oxide can be used as an ordered macroporous composite oxide catalyst.

[0086] Comparative Example 2

[0087] This comparative example provides a method for preparing a binary porous cerium manganese oxide, which is similar to the method in Comparative Example 1, except that the amount of manganese nitrate tetrahydrate used in this comparative example is 1.12 grams.

[0088] Comparative Example 3

[0089] This comparative example provides a method for preparing a binary porous cerium manganese oxide, which is similar to the method in Comparative Example 1, except that the amount of manganese nitrate tetrahydrate used in this comparative example is 1.68 grams.

[0090] Comparative Example 4

[0091] This comparative example provides a method for preparing a binary porous cerium manganese oxide, which is similar to the method in Comparative Example 1, except that the amount of manganese nitrate tetrahydrate used in this comparative example is 2.23 grams.

[0092] Comparative Example 5

[0093] This comparative example provides a method for preparing a binary porous cerium manganese oxide, which is similar to the method in Comparative Example 1, except that the amount of manganese nitrate tetrahydrate used in this comparative example is 2.79 grams.

[0094] Comparative Example 6

[0095] This comparative example provides a method for preparing binary porous cerium manganese oxide, which is similar to the method in Comparative Example 1, except that the amount of manganese nitrate tetrahydrate used in this comparative example is 3.35 grams.

[0096] Comparative Example 7

[0097] This comparative example provides a method for preparing binary porous cerium manganese oxide, which is similar to the method in Comparative Example 1, except that the amount of manganese nitrate tetrahydrate used in this comparative example is 1 gram, and the amount of cerium nitrate hexahydrate used is 1.72 grams.

[0098] Comparative Example 8

[0099] This comparative example provides a method for preparing binary porous cerium manganese oxide, which is similar to the method in Comparative Example 1, except that the amount of manganese nitrate tetrahydrate used in this comparative example is 1 gram, and the amount of cerium nitrate hexahydrate used is 3.45 grams.

[0100] Comparative Example 9

[0101] This comparative example provides a method for preparing binary porous cerium manganese oxide, which is similar to the method in Comparative Example 1, except that the amount of manganese nitrate tetrahydrate used in this comparative example is 1 gram, and the amount of cerium nitrate hexahydrate used is 5.17 grams.

[0102] Comparative Example 10

[0103] This comparative example provides a method for preparing binary porous cerium manganese oxide, which is similar to the method in Comparative Example 1, except that the amount of manganese nitrate tetrahydrate used in this comparative example is 1 gram, and the amount of cerium nitrate hexahydrate used is 6.89 grams.

[0104] Comparative Example 11

[0105] This comparative example provides a method for preparing binary porous cerium manganese oxide, which is similar to the method in Comparative Example 1, except that the amount of manganese nitrate tetrahydrate used in this comparative example is 1 gram, and the amount of cerium nitrate hexahydrate used is 8.61 grams.

[0106] Comparative Example 12

[0107] This comparative example provides a method for preparing binary porous cerium manganese oxide, which is similar to the method in Comparative Example 1, except that the amount of manganese nitrate tetrahydrate used in this comparative example is 1 gram, and the amount of cerium nitrate hexahydrate used is 10.3 grams.

[0108] Comparative Example 13

[0109] This comparative example provides a method for preparing porous metal oxides, which is similar to the method in Comparative Example 1, except that the amount of manganese nitrate tetrahydrate used in this comparative example is 0 grams (i.e., no manganese nitrate tetrahydrate is added) and the amount of cerium nitrate hexahydrate used is 1 gram.

[0110] Comparative Example 14

[0111] This comparative example provides a method for preparing porous metal oxides, which is similar to the method in Comparative Example 1, except that the amount of manganese nitrate tetrahydrate used in the comparative example is 1 gram, and the amount of cerium nitrate hexahydrate used is 0 grams (i.e., no cerium nitrate hexahydrate is added).

[0112] The main experimental parameters of Comparative Examples 1 to 14 are summarized in Table 1.

[0113] Table 1

[0114]

[0115] Figures 1 to 4 The images shown are scanning electron microscope (SEM) images of porous cerium manganese oxides from Comparative Examples 1 to 4. Figures 1 to 4 It can be seen that the average pore size of the binary porous cerium manganese oxide is around 280 nm, which is smaller than the diameter of the methyl methacrylate microspheres used as templates (340 nm to 370 nm). The smaller pore size of the porous cerium manganese oxide compared to the template microspheres is attributed to the calcination treatment during template formation and the first and second calcination processes during the formation of the porous cerium manganese oxide (also known as porous binary metal oxide), which causes a slight shrinkage of the overall structure of the microsphere template. In the porous cerium manganese oxide, highly ordered macropores are periodically interconnected through windows of approximately 100 nm, and almost no agglomerated particles are observed on the surface.

[0116] Comparing the morphology results of the porous binary metal oxides in Comparative Examples 1 to 4, Comparative Examples 1, 2, 3, and 4 exhibit uniform size and regular morphology. Therefore, it can be concluded that when the amount of cerium nitrate hexahydrate is maintained at approximately 1 gram (i.e., the molar amount of cerium nitrate hydrate is 2.24 mmol), and the calcination temperature is maintained at 550℃ for 4 hours, the macroporous catalyst exhibits good morphology. Figure 5 and Figure 6 These are, respectively, pure cerium oxide macroporous oxide of Comparative Example 13 and pure manganese oxide macroporous oxide of Comparative Example 14. From... Figure 5 and Figure 6 It can be observed that the sample of Comparative Example 13 has a more stable structure and almost no blocky particles formed by sintering. In contrast, the morphology of the sample of Comparative Example 2 is worse.

[0117] Figures 7 to 10 The images show energy-dispersive X-ray (EDS) elemental spectra of the porous binary metal oxides prepared in Comparative Examples 1 to 4, respectively. Figures 7 to 10 It can be seen that in the porous cerium manganese oxide provided by the present invention, Ce and Mn elements are uniformly dispersed on the surface of the macroporous structure.

[0118] The macroporous structure of the aforementioned porous cerium manganese oxide is suitable for gas-solid reactions. The large pore size of approximately 280 nm allows contaminants to easily enter the inner pores and come into full contact with the catalyst.

[0119] Test Example 1

[0120] This test example provides the catalytic performance test results of the porous cerium manganese oxides prepared in Comparative Examples 1, 2, 3, 4, 13, and 14. The test results are shown in [link to test results]. Figure 11 .

[0121] The catalytic performance of the porous cerium manganese oxide (cerium manganese molar ratio 1:1) of Comparative Example 1 for the NO oxidation reaction was evaluated under a gradient temperature increase of 5 vol% O2 and 500 ppm NO.

[0122] The evaluation method is as follows: Catalyst activity was tested in a fixed-bed reactor with a diameter of 30 mm and a length of 500 mm. A 0.025 g sample was weighed and placed in a quartz tube. 40 mg of cm... -3 Nitrogen gas was injected into the infrared chromatographic cell preceding the reaction to eliminate other gases inside. After background smoothing, 5 mg cm⁻¹ gas was injected. -3 Nitric oxide, as a pollutant, and 2.8 mg cm -3 Oxygen; heated from 50°C to 100°C at a heating rate of 10°C / min, and then heated to 450°C at a heating rate of 2°C / min.

[0123] In practical applications, the catalytic activity of catalysts in the low-temperature region is more valuable than that in the high-temperature region. Therefore, the following mainly compares the catalytic activities of Comparative Examples 1 to 4, Comparative Example 13 and Comparative Example 14 in the low-temperature region:

[0124] from Figure 11 It can be seen that at 250℃, the order of NO conversion activity exhibited by each sample is: Comparative Example 2 > Comparative Example 3 > Comparative Example 4 > Comparative Example 1 > Comparative Example 14 > Comparative Example 13.

[0125] Furthermore, within the testing range of 100-400℃, the highest NOx conversion rate of Comparative Example 1 was at 322℃, that of Comparative Example 2 was at 325℃, that of Comparative Example 3 was at 320℃, and that of Comparative Example 4 was at 331℃; while the highest NOx conversion rate of Comparative Example 13 reached 400℃ and that of Comparative Example 14 reached 350℃.

[0126] Example 1

[0127] This embodiment provides a method for preparing a ternary porous metal oxide, including:

[0128] 1. Pour 120 ml of refined methyl methacrylate into a 1000 ml four-necked flask, then add 450 ml of deionized water, purge with nitrogen and turn on the condenser.

[0129] Potassium persulfate was heated to dissolve it. The mixture was stirred at 300 rpm / min and heated to 80°C. Once the solution in the four-necked flask reached 80°C, the potassium persulfate solution at 80°C was added to the four-necked flask containing the methyl methacrylate solution to carry out the polymerization reaction. The mixture was stirred for 1-2 hours.

[0130] The product of the polymerization reaction was filtered, and the filtrate was placed in a 50 mL centrifuge tube and centrifuged at 3000 rpm / min for 10-11 hours. After drying for 24 hours, the ordered microsphere template agent was obtained.

[0131] 2. Place 1 gram of cerium nitrate hexahydrate, 1.12 grams of manganese acetate tetrahydrate and 0.0636 grams of potassium nitrate into a 100 ml beaker, then pour in 50 ml of methanol and ethylene glycol in a volume ratio of 1:4. Turn on the stirrer and set it to 500 rpm / min to heat to 50°C. Stir until the metal salt is completely dissolved to obtain a metal precursor solution.

[0132] Three grams of dried microspheres were added to the above metal precursor solution and vacuum impregnated for 24 hours. The impregnated fragmented microspheres were filtered and dried for 24 hours. The fragmented microspheres completely impregnated with metal salts were placed in a tube furnace and calcined by air circulation. First, the temperature was heated to 300°C and held for 3 hours for the first calcination. Then, the temperature was heated to 550°C and held for 4 hours for the second calcination to obtain a ternary porous metal oxide. This ternary porous metal oxide can be used as a trimetallic ordered macroporous composite oxide catalyst.

[0133] Figure 16 The image shows a SEM image of the microsphere template agent prepared in Example 1. It can be seen that the microsphere template agent prepared in this invention has a particle size of 340 nm to 370 nm, and the microspheres are arranged in an ordered manner.

[0134] Example 2

[0135] This embodiment provides a method for preparing a ternary porous metal oxide, which is similar to the method in Example 1, except that the amount of potassium nitrate used in this embodiment is 0.106 grams.

[0136] Example 3

[0137] This embodiment provides a method for preparing a ternary porous metal oxide, which is similar to the method in Example 1, except that the amount of potassium nitrate used in this embodiment is 0.1696 grams.

[0138] Example 4

[0139] This embodiment provides a method for preparing a ternary porous metal oxide, which is similar to the method in Example 1, except that the amount of potassium nitrate used in this embodiment is 0.212 grams.

[0140] Example 5

[0141] This embodiment provides a method for preparing a ternary porous metal oxide, which is similar to the method in Example 1, except that the amount of potassium nitrate used in this embodiment is 0 grams and the amount of sodium nitrate is 0.0636 grams.

[0142] Example 6

[0143] This embodiment provides a method for preparing a ternary porous metal oxide, which is similar to the method in Example 1, except that the amount of potassium nitrate used in this embodiment is 0 grams and the amount of sodium nitrate is 0.106 grams.

[0144] Example 7

[0145] This embodiment provides a method for preparing a ternary porous metal oxide, which is similar to the method in Example 1, except that the amount of potassium nitrate used in this embodiment is 0 grams and the amount of sodium nitrate is 0.1696 grams.

[0146] Example 8

[0147] This embodiment provides a method for preparing a ternary porous metal oxide, which is similar to the method in Example 1, except that the amount of potassium nitrate used in this embodiment is 0 grams and the amount of lithium nitrate trihydrate is 0.0636 grams.

[0148] Example 9

[0149] This embodiment provides a method for preparing a ternary porous metal oxide, which is similar to the method in Example 1, except that the amount of potassium nitrate used in this embodiment is 0 grams and the amount of lithium nitrate trihydrate is 0.106 grams.

[0150] Example 10

[0151] This embodiment provides a method for preparing a ternary porous metal oxide, which is similar to the method in Example 1, except that the amount of potassium nitrate used in this embodiment is 0 grams and the amount of lithium nitrate trihydrate is 0.1696 grams.

[0152] Example 11

[0153] This embodiment provides a method for preparing a ternary porous metal oxide, which is similar to the method in Example 1, except that the amount of potassium nitrate used in this embodiment is 0 grams and the amount of lithium nitrate trihydrate is 0.212 grams.

[0154] The main experimental parameters of Examples 1 to 11 above are summarized in Table 2.

[0155] Table 2

[0156]

[0157]

[0158] The morphological observation results of the ternary porous metal oxides in Examples 1 to 11 are summarized in Table 3.

[0159] Table 3

[0160]

[0161] The pore size of the samples in Examples 1 to 11 in Table 3 is 200-350 nm.

[0162] As can be seen from Tables 2 and 3, the size of the macropores, surface particles, and pore window size are related to the amount of alkali metal salts (potassium nitrate, sodium nitrate, and lithium nitrate) used. A detailed analysis follows:

[0163] (1) Combining Examples 1 to 4 with Comparative Example 2, it can be seen that when a small amount of potassium nitrate is added, the pore size is uniform and the pore window size is about 30 nm; when the amount of potassium nitrate is increased, a few particles appear on the macroporous catalyst; when the amount of potassium nitrate is gradually increased, the size of the nanoparticles increases significantly; when the amount of potassium nitrate is further increased, the macroporous structure is damaged to a certain extent.

[0164] (2) Comparing Examples 5 to 7 with Comparative Example 2, it can be seen that when a small amount of sodium nitrate is added, no particles appear; when the amount of sodium nitrate is continued, a few spherical particles of uneven size appear on the surface of the pore structure; when the amount of sodium nitrate is gradually increased, more particles appear on the surface of the pore structure.

[0165] (3) Comparing Examples 8 to 11 with Comparative Example 2, it can be seen that when a small amount of lithium nitrate is added, uniform macropores are exhibited; when the amount of lithium nitrate is further increased, no particles appear on the surface of the pore structure; when the amount of lithium nitrate is gradually increased, a few particles appear, and the macropore structure is stable; when the amount of sodium nitrate is at its maximum, more particles appear on the surface of the macropore structure.

[0166] Figures 17 to 27 The images shown are scanning electron microscope (SEM) images of the ternary porous metal oxides from Examples 1 to 11. It can be seen that the ternary porous metal oxides provided by this invention have an average macropore diameter of approximately 220 nm, which is smaller than the diameter of the methyl methacrylate microspheres used as templates (340 nm to 370 nm). The smaller pore size of the ternary porous oxides compared to the microspheres is attributed to the calcination treatment during template formation and the first and second calcination treatments during the formation of the ternary porous oxides, which cause a slight shrinkage of the overall structure of the microsphere template. In the ternary porous metal oxides, highly ordered macropores are periodically interconnected through windows of approximately 50 nm.

[0167] Comparing the morphology results of the ternary porous metal oxides in the above embodiments, Examples 1, 2, 5, 6, 8, and 9 exhibit uniform size and regular morphology, and almost no agglomerated particles are observed on the surface. This indicates that adding an appropriate amount of alkali metal will not disrupt the ordered macroporous structure and will not generate a large number of agglomerated particles.

[0168] Figures 28 to 31The images shown are, in order, energy-dispersive X-ray spectral elemental spectra of the ternary porous metal oxides prepared in Examples 1, 2, 5, and 6. It can be seen that in the ternary porous metal oxides provided by this invention, Ce, Mn, and alkali metal elements are uniformly dispersed on the surface of the macroporous structure.

[0169] The macroporous structure of the aforementioned ternary porous metal oxide is suitable for gas-solid reactions. The large pore size of approximately 220 nm makes it easy for contaminants to enter the inner pores and come into full contact with the catalyst.

[0170] Furthermore, XPS characterization of the ternary porous metal oxides revealed that, compared to binary porous metal oxides, the ternary porous oxides with added alkali metals exhibited increased active oxygen content and altered the Ce3+ / Ce4+ ratio, which contributed to improved catalytic performance.

[0171] Test Example 2

[0172] This test example provides the performance test results of the ternary porous metal oxides of the above embodiments.

[0173] (1) Catalytic activity test

[0174] according to Figure 11 The catalytic performance of the ternary porous metal oxides in Examples 1 to 11 was tested using the method described above. Figures 12 to 14 The results are from the test.

[0175] Figure 12 The NO conversion results are for the ternary porous metal oxides used in Examples 1 to 4. Figure 12 It can be seen that at 250℃, the order of NO conversion activity exhibited by each sample is: Example 1 > Example 2 > Example 3 > Example 4.

[0176] Figure 13 The NO conversion results are for the ternary porous metal oxides used in Examples 5 to 7. From... Figure 13 It can be seen that at 250℃, the order of NO conversion activity exhibited by each sample is: Example 6 > Example 5 > Example 7.

[0177] Figure 14 The NO conversion results are for the ternary porous metal oxides used in Examples 8 to 11. From... Figure 14 It can be seen that at 250℃, the order of NO conversion activity exhibited by each sample is: Example 8 > Example 9 > Example 10 > Example 11.

[0178] (2) Catalytic stability test

[0179] The catalytic stability of the binary porous metal oxide in Comparative Example 2 was tested in a fixed-bed reactor with a diameter of 30 mm and a length of 500 mm. 0.025 g of sample was weighed and placed in a quartz tube. 40 mg of cm... -3 Nitrogen gas was injected into the infrared chromatographic cell preceding the reaction to eliminate other gases inside. After background smoothing, 5 mg cm⁻¹ gas was injected. -3 Nitric oxide, as a pollutant, and 2.8 mg cm -3 Oxygen; heated from 50°C to 100°C at a rate of 10°C / min, then further heated to 450°C at a rate of 2°C / min. Test results are as follows: Figure 15 As shown in Figure 1 and Table 4.

[0180] The above experiments were performed on the ternary metal oxide of Example 5, and the experimental results are shown below. Figure 32 As shown in Table 5.

[0181] The conversion rate formulas in Tables 4 and 5 are as follows:

[0182] NO conversion rate = (NO 进口 -NO 出口 ) / NO 进口 ×100%.

[0183] Table 4

[0184] Conversion rate at 250℃ (%) Highest conversion rate (%) Loop 1 63.2 98 Loop 2 62.6 98 Cycle 3 62.4 97.8 Cycle 4 62.2 97.4 Cycle 5 58.8 97

[0185] Table 5

[0186]

[0187]

[0188] from Figure 15 As shown in Table 4, the catalyst prepared from the porous metal oxide in Comparative Example 2 maintained a high NO conversion rate even after five catalytic cycles; the NO conversion rate retention rate reached 98.9% after five cycles. Figure 32 As shown in Table 5, the activity of the catalyst prepared by the ternary porous oxide remained generally stable with the increase of the number of cycles. Under the test conditions of 250℃, the conversion rate decreased by less than 3% in each test, and the highest conversion rate in the range of 300-500℃ decreased by less than 0.5% each time. Compared with the binary porous metal oxide of Comparative Example 2, the ternary metal oxide of Example 5 has higher catalytic stability. Specifically, the conversion rate of the catalyst prepared by the ternary porous metal oxide is still higher than that of the binary metal oxide after the same number of cycles at the same temperature. Furthermore, the conversion rate of the ternary porous oxide can reach 65-74% at a low temperature of 250℃, and the highest conversion rate can reach 100% in the range of 300-500℃.

[0189] The above results demonstrate that by adding alkali metal elements to cerium-manganese raw materials, the present invention can improve the catalytic stability and catalytic effect of ternary porous metal oxides.

Claims

1. A method for preparing a ternary porous metal oxide, the method comprising: The microsphere template agent is impregnated in a solution of metal precursor, and the impregnated microsphere template agent is subjected to a first calcination and a second calcination in sequence to obtain the ternary porous metal oxide. The metal precursor includes a cerium source, a manganese source, and an alkali metal source; The first calcination temperature is 300-350℃, and the first calcination time is 3h-4h; The second calcination temperature is 500-550℃, and the second calcination time is 4-4.5 hours. The molar ratio of the alkali metal source to the cerium source is 0.2-0.5:1; The microsphere template agent includes polymethyl methacrylate microspheres, and the alkali metal element in the alkali metal source includes one or more combinations of lithium, sodium, and potassium.

2. The preparation method according to claim 1, wherein, The microsphere template agent has a particle size of 300nm-500nm.

3. The preparation method according to claim 1, wherein, The preparation method of the polymethyl methacrylate microspheres includes: In a protective atmosphere, methyl methacrylate is mixed with an initiator and subjected to a polymerization reaction to obtain the polymethyl methacrylate microspheres.

4. The preparation method according to claim 3, wherein, The initiator includes potassium persulfate.

5. The preparation method according to claim 3, wherein, The polymerization reaction is carried out at a temperature of 70-90℃ for 1-2 hours.

6. The preparation method according to claim 1, wherein, The molar ratio of the cerium source to the manganese source is 1-6:1-10.

7. The preparation method according to claim 1, wherein, The molar ratio of the cerium source to the manganese source is 1-5:1-5.

8. The preparation method according to claim 1, wherein, The cerium source includes cerium salts.

9. The preparation method according to claim 8, wherein, The cerium salts include cerium nitrate and / or cerium acetate.

10. The preparation method according to claim 1, wherein, The manganese source includes manganese salts.

11. The preparation method according to claim 10, wherein, The manganese salt includes manganese nitrate and / or manganese acetate.

12. The preparation method according to claim 1, wherein, The alkali metal source includes alkali metal salts.

13. A ternary porous metal oxide, obtained by the preparation method according to any one of claims 1-12.

14. The ternary porous metal oxide according to claim 13, wherein, The pore size of the ternary porous metal oxide is 200-350 nm.

15. A catalyst comprising the ternary porous metal oxide of claim 13 or 14, wherein the catalyst is a CO oxidation catalyst or a NOx oxidation catalyst.

16. A catalyst made from the ternary porous metal oxide of claim 13 or 14; said catalyst being a CO oxidation catalyst or a NOx oxidation catalyst.

Citation Information

Patent Citations

  • Catalyst in which potassium-manganese-cerium composite oxide is supported in 3DOM (three-dimensionally ordered macroporous materials), and preparation and application of catalyst

    CN104607179A

  • Macroporous Ce-Zr based composite metal oxide catalyst, preparation method, and application thereof

    CN106582665A

  • Multifunctional mesoporous cerium-base solid solution catalyst for catalytic purification of automobile exhaust

    CN109529859A